Preparation of transition metal sulfide nanoparticles via hydrothermal route - Pua, F.L.; Chia, C.H.; Zakari, S.; Liew, T.K.; Yarmo, M.A.; Huang, N.M. (Penerbit Universiti Kebangsaan Malaysia, 2010)
Nano sized copper sulfide, iron sulfide and molybdenum sulfide were successfully synthesised via a simple hydrothermal method. Sodium thiosulfate pentahydrate (Na2S2O3Ã5H2O) and hydroxylamine sulfate ((H3NO)2ÃH 2SO4) were used as the starting materials and reacted with the transition metal source at 200Â°C for 90 min. The products were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX) and Fourier transform infrared spectroscopy (FTIR). Spherical shape CuS and FeS2 nanoparticles with high crystallinity were successfully produced. The transmission electron micrographs revealed the well-dispersibility of the produced nanoparticles. Scanning electron micrograph showed the MoS 2 nanoparticles possessed a spherical shape with sheet-like structure covering on the outer surface of the particles.